Kompromi Sistem Hukum Adat, Islam, dan Negara dalam Tradisi Greun Masyarakat Lamaholot (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2025)
The implementation of the Greun tradition in Lamaholot customary marriage generates normative tensions when clan-based marriage restrictions conflict with the freedom of marriage guaranteed under the concept of Mahram An-Nikah in Islamic law. This study aims to analyze how the Lamaholot Muslim community manages and negotiates the inconsistencies between Greun customary law, Islamic law, and state law within the framework of legal pluralism. Utilizing an empirical qualitative method with a sociology of law approach, this case study in Leworaja Village and Pantai Harapan Village, Lembata Regency, employs in-depth interviews, observation, and document analysis. The findings reveal that the community mitigates potential normative conflicts by redefining the status of Greun from a binding customary imperative into a cultural recommendation classified as 'urf ṣaḥīḥ, provided it does not contradict Islamic law. This study concludes that the compromise between legal systems occurs through adaptive socio-cultural negotiation rather than formal legal reform. The novelty of this research lies in unveiling a bottom-up reconciliation model that demonstrates the internal flexibility of Lamaholot customary law in harmoniously integrating customary norms, religion, and morality.